A Synthetic Factor VIII Peptide of Eight Amino Acid Residues (1677-1684) Contains the Binding Region of an Anti-Factor VIII Antibody which Inhibits the Binding of Factor VIII to von Willebrand Factor - Foster, Paul A; Fulcher, Carol A; Houghten, Richard A; Zimmerman, Theodore S (Thrombosis and Haemostasis, 1990)
The monoclonal anti-factor VIII (FVIII) antibody C4 has previously been reported to inhibit the binding of purified FVIII to immobilized von Willebrand factor (vWF). The binding area of C4 was identified to be within fifteen amino acid residues (1670-1684) based on the ability of a synthetic FVIII peptide consisting of amino acid residues 1670-1684 to completely inhibit the binding of C4 to FVIII. We now report the further localization of the binding region of C4 to within eight amino acid residues (1677-1684) of FVIII light chain. Nine new overlapping FVIII peptides were synthesized based on the amino acid sequence of the acidic region of FVIII light chain and tested, along with seven previously tested peptides, for the ability to inhibit C4 binding to FVIII in an ELISA assay. Three synthetic FVIII peptides 1670-1684, 1675-1690, and 1677-1684 demonstrated dose dependent inhibition of C4 binding to FVIII. The three reactive peptides contain residues 1677-1684 in common. Since C4 can completely inhibit the binding of FVIII to vWF, this report further localizes an eight amino acid residue region of FVIII which may be important in the mediation of vWF binding.